2022
DOI: 10.3390/foods11213491
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Development of Heterocyclic Aromatic Amines in Fried Bacon and in the Remaining Oil after Pan-Frying in Five Different Vegetable Oils

Abstract: The physicochemical properties of five vegetable oils (peanut, corn, rapeseed, sunflower seed, and soybean) and their impact on the development of heterocyclic aromatic amines (HAAs) in pan-fried bacon and in the remaining oil were investigated. Corn oil led to the lowest total free amino acids (FAAs) contents and glucose content of fried bacon (p < 0.05) and rapeseed oil led to the lowest creatine content of fried bacon (p < 0.05). Bacon fried in corn oil had the highest HAA contents (p < 0.05). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…It is also added that amino acids and Maillard and Strecker reactions are involved in MeIQx formation [56]. As a matter of fact, it has been reported that glycine, lysine, alanine, threonine, and serine play a role in the formation of MeIQx, and lysine, aspartic acid, isoleucine, and phenylalanine play a role in the formation of PhIP [61]. In this respect, the high carbohydrate (44.2%) and protein (17.8%) content of cumin provides the appropriate substrate conditions for the formation of the Maillard reaction during cooking [26,62].…”
Section: Total Haas Of the Meatballsmentioning
confidence: 99%
“…It is also added that amino acids and Maillard and Strecker reactions are involved in MeIQx formation [56]. As a matter of fact, it has been reported that glycine, lysine, alanine, threonine, and serine play a role in the formation of MeIQx, and lysine, aspartic acid, isoleucine, and phenylalanine play a role in the formation of PhIP [61]. In this respect, the high carbohydrate (44.2%) and protein (17.8%) content of cumin provides the appropriate substrate conditions for the formation of the Maillard reaction during cooking [26,62].…”
Section: Total Haas Of the Meatballsmentioning
confidence: 99%